Geospatial Assessment of Freshwater Quality for Heavy Metals and its Potential Health Risks Using Geoinformatics and Water Index Models in Gilgit-Baltistan-Pakistan - Naila Jabeen; Lubna Ghazal; Humaira Kanwal; Tayyab Raza Fraz; Muhammad Farrakh Nawaz; Liaquat Karim; Faten Khalid Karim; Samih M. Mostafa; Altaf Hussain Lahori (International Journal of Environmental Research, 2026)
Access to safe drinking water is a growing global challenge, with billions of people exposed to water scarcity and contamination risks. Heavy metals in drinking water are of particular concern due to their toxic effects on human health and ecosystems. This study assessed the drinking water quality of Hunza Valley, Gilgit-Baltistan, Pakistan, where no comprehensive geospatial evaluation had previously been conducted. A total of 66 water samples from springs and glaciers were analyzed for physico-chemical parameters and heavy metals (Fe, Ni, Cd, Cr-VI, As, and Pb). Statistical analysis (correlation, principal component analysis and cluster analysis), water quality indices (Water Quality Index and Synthetic Pollution Index), human health risk assessment (Hazard Quotient and Hazard Index) and geostatistical interpolation (Ordinary Kriging) were employed. Results showed that As (77%), Pb (34%), Cd (25%), and Cr-VI (9%) exceeded WHO limits, while Fe and Ni remained within permissible levels. WQI classified 59% of samples as unfit for human consumption, while SPI designated 26% as unsafe. PCA extracted four significant factors explaining 67% of total variance, and hotspot mapping highlighted Aliabad, Dorkhun, and Ganish as most contaminated villages. The hazard quotient and hazard index for non-carcinogenic health risk showed very few samples with significant health risk. The geospatial maps of health risk showed higher geospatial variability for arsenic, lead and iron whereas low variations were observed for cadmium, chromium and nickel. The TCRI values revealed As, Cd, Cr, Pb and Ni pose significant carcinogenic health risk with geospatial variation highlighting the western side of the district. The findings emphasize the urgent need for feasibility studies for treatment facilities, regular monitoring, cancer specific health risk studies to protect public health in Hunza Valley. This research provides a framework for sustainable water management aligned with SDG-6.

Regulatory mechanisms and signalling cascades in plant adaptation to heavy metal toxicity - A. M. Shah; S. Manzoor; M. T. Altaf; Z. Bayramoğlu; S. M. Popescu; S. Mansoor (International Journal of Environmental Science and Technology, 2026)

Iron-Loaded Biochar Ameliorates Cadmium-Induced Phytotoxicity in Rapeseed by Modulating Cd Uptake, Nutrient Homeostasis, and Antioxidative Systems - Sumra Siddique Abbasi; Hafiz Saqib Hayat; Hua-Yi Chen; Muhammad Mohsin Altaf; Mudawi M. Nour; Afrah E. Mohammed (Journal of Soil Science and Plant Nutrition, 2026)

Phenylalanine ammonia lyase as a molecular driver of rutin enrichment: evidence from cloning and localization studies in buckwheat - Mohsin Altaf Hajini; Saika Bashir; Mansoor Showkat; Majid Rashid; Parvaze Ahmad Sofi; Tanveer Ali Dar; Ajaz A. Malik; Nitin Jain; M. Ashraf Bhat; Sajad Majeed Zargar (The Nucleus, 2026)

Biological agents and biomaterials for environmental remediation: applications in water, soil, and air - I U. Islam; S. Bano; M. Mehwish; M. Altaf; R. Shoaib; X. Hu; D. Li; Z. Xiaolian; W. Fatima; N. Shah; X. Wang; E. Yabalak (International Journal of Environmental Science and Technology, 2026)

Field evaluation of single-site and combination fungicides for sustainable management of rice blast and yield enhancement in temperate conditions of Kashmir - Heena Altaf; Fayaz Mohiddin; Asif Bashir Shikari; M. Ashraf Ahangar; Fehim J. Wani; Zakir Amin; Tabasum Manzoor; Nazir A. Bhat (Indian Phytopathology, 2026)

Role of HMGB1 in Neuroinflammation - Amir Ajoolabady; Rizwan Ahmad; Glowi Alasiri; Mohammed Alaidarous; Randa Mohammad Ibrahim; Bonglee Kim; Altaf A. Abdulkhaliq; Anwar Borai; Jaakko Tuomilehto; Bahauddeen M. Alrfaei; Jun Ren; Johra Khan; et al. (Molecular Neurobiology, 2026)

Carboxymethyl cellulose: Structural modifications and their impact on barrier and mechanical properties for sustainable food packaging - Batool Esmat; Shumaila Bibi; Mohamed Mohamed Soliman; Hamdy Khamees Thabet; Muhammad Ahmad Wattoo; Muhammad Altaf Nazir; Zeinhom M. El-Bahy; Aziz ur Rehman (Journal of Stored Products Research, 2026)

Overexpression of Agr quorum sensing system in uropathogenic Staphylococcus aureus in response to simulated urinary metabolic conditions enhancing growth and virulence - Yuvarajan Subramaniyan; M. Mujeeburahiman; Altaf Khan; Punchappady Devasya Rekha (Medical Microbiology and Immunology, 2025)

Secondary metabolite and antioxidant enzyme dynamics underpin resistance to Magnaporthe oryzae in rice genotypes of the Kashmir Valley - Heena Altaf; Fayaz A. Mohiddin; Asif Bashir Shikari; M. Ashraf Ahangar; Fehim J. Wani; Zakir Amin; Tabasum Manzoor; Raheel Shafeeq Khan; Noor-Ul-Ain; Mohammad Saleem Dar; Hattan A. Alharbi; Rajesh N. Udavant (Physiological and Molecular Plant Pathology, 2025)

Plants Response to Different Abiotic Stresses - Sami Jan; M. Ashraf Bhat; Akshay Kumar; M. Altaf Wani; Farooq Ahmad Bhat; Raihana H. Kanth; A. B. Shikari; Haleema Bano; Tabasum Manzoor; Heena Altaf; Noor-ul-Ain; Zafir Ahmad Naik (Journal of Crop Health, 2025)

Anti-breast cancer potential of fluoro-containing triazole-synthesized hybrid molecules: In-vitro screening and Force Field-based molecular dynamics approach - Malik Nasibullah; Altaf Ahmad Shah; Zainab Feroz; Pritee Chunarkar Patil; Priyanka Sharma; Zainab M. Almarhoon; Salman Akhtar; Sahir Sultan Alvi; Mohd Asif (Next Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Selenium priming enhances the expression of Sec A translocase in common bean (Phaseolus vulgaris L.) - Madeeha Mansoor; Asmat Farooq; Jebi Sudan; Pandit Arif; Tamana Khan; Aaqif Zafar; Mohsin Altaf Hajini; Mudasir A. Mir; Parvaze A. Sofi; M. Ashraf Bhat; Sajad Majeed Zargar (The Nucleus, 2025)

Synthesis of highly efficient bifunctional Nd2S3-MoSe2 heterostructure electrocatalyst for overall water-splitting - M. Abdul; Xuefan Jiang; Nouf H. Alotaibi; Reem Abdulrahman Habab; Altaf Ur Rahman; Jing Bo (Fuel, 2025)

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Etiology, management, and host response of cold-tolerant maize germplasm for common rust disease of maize under temperate conditions - Heena Altaf; M. Ashraf Ahangar; Tabassum Manzoor; Fayaz Mohiddin (Cereal Research Communications, 2025)

Retention forestry as a climate solution: Assessing biomass, soil carbon and albedo impacts in a northern temperate coniferous forest - Kangyu So; Cheryl A. Rogers; Yiyao Li; M. Altaf Arain; Alemu Gonsamo (Science of The Total Environment, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Corrigendum to “Physical workplaces and human well-being: A mixed-methods study to quantify the effects of materials, windows, and representation on biobehavioral outcomes” [Building and Environment 224 (2022) 109516] - Isabella P. Douglas; Elizabeth L. Murnane; Lucy Zhang Bencharit; Basma Altaf; Jean Marcel dos Reis Costa; Jackie Yang; Meg Ackerson; Charu Srivastava; Michael Cooper; Kyle Douglas; Jennifer King; Pablo E. Paredes; et al. (Building and Environment, 2024)

Flood resilience assessment from the perspective of urban (in)formality in Surat, India: Implications for sustainable development - Ali Jamshed; Chirag Patel; Anshul Puriya; Nimra Iqbal; Irfan Ahmad Rana; Joanna M. McMillan; Rajiv Pandey; Shahbaz Altaf; Rana Tahir Mehmood; Umair bin Saad (Natural Hazards, 2024)
Urbanization has resulted in increasing the pace of informality, specifically in developing countries like India. Informality is taking place at locations that are exposed to various hazards, and therefore, resilience building of both informal and formal settlements is needed to achieve sustainable development. Resilience assessment is key in defining appropriate area-specific resilience measures. Given that, this research assesses the resilience of formal and informal settlements of Surat city in India and presents implications for sustainable development. To assess resilience, an indicator-based approach was taken, using a household survey to collect the data. Analysis suggests that the resilience of formal and informal settlements is significantly different. Key differences were found in physical and institutional resilience, where informal settlements were found to be significantly less resilient than formal settlements. Several measures, such as gender-sensitive education and livelihood programs, as well as mobile water and sanitation, have positive implications for sustainable development. Overall, the study can guide disaster managers and policy makers to adopt a strategic and more targeted approach to strengthen resilience and achieve sustainable development.

Different climate conditions drive variations in gross primary productivity and woody biomass accumulation in a temperate and a boreal conifer forest in Canada - Paulina F. Puchi; Myroslava Khomik; Warren Helgason; M. Altaf Arain; Daniele Castagneri (Agricultural and Forest Meteorology, 2024)

The impact of spongy moth (Lymantria dispar dispar) defoliation on carbon balance of a temperate deciduous forest in North America - Lejla Latifovic; M. Altaf Arain (Agricultural and Forest Meteorology, 2024)

The chemical composition and biological activities of plant essential oils against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Nimra Altaf; Muhammad Irfan Ullah; Muhammad Arshad; Muhammad Afzal; Laila A. Al‑Shuraym; Naunain Mehmood; Zafar Hayat; Samy M. Sayed (Journal of Plant Diseases and Protection, 2024)

Forest carbon uptake as influenced by snowpack and length of photosynthesis season in seasonally snow-covered forests of North America - Julia C. Yang; David R. Bowling; Kenneth R. Smith; Lewis Kunik; Brett Raczka; William R.L. Anderegg; Michael Bahn; Peter D. Blanken; Andrew D. Richardson; Sean P. Burns; Gil Bohrer; Ankur R. Desai; et al. (Agricultural and Forest Meteorology, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Evaluating the effectiveness of different variable retention harvesting treatments on forest carbon uptake using remote sensing - Nur Hussain; M. Altaf Arain; Shusen Wang; William C. Parker; Ken A. Elliott (Remote Sensing Applications: Society and Environment, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Impacts of heat and drought on the dynamics of water fluxes in a temperate deciduous forest from 2012 to 2020 - Arango Ruda Elizabeth; M. Altaf Arain (Agricultural and Forest Meteorology, 2024)

High doses of clethodim-based herbicide GrassOut Max poses reproductive hazard by affecting male reproductive function and early embryogenesis in Swiss albino mice - Reyon Dcunha; Sandhya Kumari; Mohd Altaf Najar; Anjana Aravind; Keerthana Sandesh Suvarna; Ananda Hanumappa; Sadhana P. Mutalik; Srinivas Mutalik; Sneha Guruprasad Kalthur; G.K. Rajanikant; Sazada Siddiqui; Sulaiman Alrumman; et al. (Chemosphere, 2023)

Melatonin Mitigates Salt-Induced Growth Inhibition Through the Regulation of Carbohydrate and Nitrogen Metabolism in Tomato Seedlings - Mohammad Shah Jahan; Guihua Li; Dasen Xie; Reham Farag; Md. Mahadi Hasan; Nadiyah M. Alabdallah; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Muhammad Zeeshan; Jamal Nasar; Muhammad Ahsan Altaf; Md Atikur Rahman (Journal of Soil Science and Plant Nutrition, 2023)

Satellite-based land surface temperature and soil moisture observations accurately predict soil respiration in temperate deciduous and coniferous forests - Lelia Weiland; Cheryl A. Rogers; Camile Sothe; M. Altaf Arain; Alemu Gonsamo (Agricultural and Forest Meteorology, 2023)

Snow-corrected vegetation indices for improved gross primary productivity assessment in North American evergreen forests - Ran Wang; David R. Bowling; John A. Gamon; Kenneth R. Smith; Rong Yu; Gabriel Hmimina; Masahito Ueyama; Asko Noormets; Thomas E. Kolb; Andrew D. Richardson; Charles P.A. Bourque; Rosvel Bracho; et al. (Agricultural and Forest Meteorology, 2023)

Tree-ring growth varies with climate and stand density in a red pine plantation forest in the Great Lakes region of North America - Shawn M. McKenzie; William C. Parker; Michael F.J. Pisaric; M. Altaf Arain (Dendrochronologia, 2023)

The effect of relative humidity on eddy covariance latent heat flux measurements and its implication for partitioning into transpiration and evaporation - Weijie Zhang; Martin Jung; Mirco Migliavacca; Rafael Poyatos; Diego G. Miralles; Tarek S. El-Madany; Marta Galvagno; Arnaud Carrara; Nicola Arriga; Andreas Ibrom; Ivan Mammarella; Dario Papale; et al. (Agricultural and Forest Meteorology, 2023)

Comparison of tree-ring growth and eddy covariance-based ecosystem productivities in three different-aged pine plantation forests - Shawn M. McKenzie; Michael F. J. Pisaric; M. Altaf Arain (Trees, 2021)

Role of ROS generation in acute genotoxicity of azoxystrobin fungicide on freshwater snail Lymnaea luteola L - Daoud Ali; Khalid E. Ibrahim; Seik Altaf Hussain; Mohamed M. Abdel-Daim (Environmental Science and Pollution Research, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Seasonal variability of forest sensitivity to heat and drought stresses: A synthesis based on carbon fluxes from North American forest ecosystems - Bing Xu; M. Altaf Arain; T. Andrew Black; Beverly E. Law; Gilberto Z. Pastorello; Housen Chu (Global Change Biology, 2020)
Climate extremes such as heat waves and droughts are projected to occur more frequently with increasing temperature and an intensified hydrological cycle. It is important to understand and quantify how forest carbon fluxes respond to heat and drought stress. In this study, we developed a series of daily indices of sensitivity to heat and drought stress as indicated by air temperature ( T a ) and evaporative fraction (EF). Using normalized daily carbon fluxes from the FLUXNET Network for 34 forest sites in North America, the seasonal pattern of sensitivities of net ecosystem productivity (NEP), gross ecosystem productivity (GEP) and ecosystem respiration (RE) in response to T a and EF anomalies were compared for different forest types. The results showed that warm temperatures in spring had a positive effect on NEP in conifer forests but a negative impact in deciduous forests. GEP in conifer forests increased with higher temperature anomalies in spring but decreased in summer. The drought‐induced decrease in NEP, which mostly occurred in the deciduous forests, was mostly driven by the reduction in GEP. In conifer forests, drought had a similar dampening effect on both GEP and RE, therefore leading to a neutral NEP response. The NEP sensitivity to T a anomalies increased with increasing mean annual temperature. Drier sites were less sensitive to drought stress in summer. Natural forests with older stand age tended to be more resilient to the climate stresses compared to managed younger forests. The results of the Classification and Regression Tree analysis showed that seasons and ecosystem productivity were the most powerful variables in explaining the variation of forest sensitivity to heat and drought stress. Our results implied that the magnitude and direction of carbon flux changes in response to climate extremes are highly dependent on the seasonal dynamics of forests and the timing of the climate extremes.

Cryptic phenology in plants: Case studies, implications, and recommendations - Loren P. Albert; Natalia Restrepo‐Coupe; Marielle N. Smith; Jin Wu; Cecilia Chavana‐Bryant; Neill Prohaska; Tyeen C. Taylor; Giordane A. Martins; Philippe Ciais; Jiafu Mao; M. Altaf Arain; Wei Li; et al. (Global Change Biology, 2019)
Plant phenology—the timing of cyclic or recurrent biological events in plants—offers insight into the ecology, evolution, and seasonality of plant‐mediated ecosystem processes. Traditionally studied phenologies are readily apparent, such as flowering events, germination timing, and season‐initiating budbreak. However, a broad range of phenologies that are fundamental to the ecology and evolution of plants, and to global biogeochemical cycles and climate change predictions, have been neglected because they are “cryptic”—that is, hidden from view (e.g., root production) or difficult to distinguish and interpret based on common measurements at typical scales of examination (e.g., leaf turnover in evergreen forests). We illustrate how capturing cryptic phenology can advance scientific understanding with two case studies: wood phenology in a deciduous forest of the northeastern USA and leaf phenology in tropical evergreen forests of Amazonia. Drawing on these case studies and other literature, we argue that conceptualizing and characterizing cryptic plant phenology is needed for understanding and accurate prediction at many scales from organisms to ecosystems. We recommend avenues of empirical and modeling research to accelerate discovery of cryptic phenological patterns, to understand their causes and consequences, and to represent these processes in terrestrial biosphere models.

Solar‐induced chlorophyll fluorescence exhibits a universal relationship with gross primary productivity across a wide variety of biomes - Jingfeng Xiao; Xing Li; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2019)

The Use of Multi-parametric Biomarker Profiles May Increase the Accuracy of ASD Prediction - Wail M. Hassan; Laila Al-Ayadhi; Geir Bjørklund; Altaf Alabdali; Salvatore Chirumbolo; Afaf El-Ansary (Journal of Molecular Neuroscience, 2018)

Stable carbon and nitrogen isotopic composition of PM10 over Indo-Gangetic Plains (IGP), adjoining regions and Indo-Himalayan Range (IHR) during a winter 2014 campaign - Avirup Sen; Supriya G. Karapurkar; Mohit Saxena; Damodar M. Shenoy; Abhijit Chaterjee; Anil K. Choudhuri; Trupti Das; Altaf H. Khan; Jagdish Chandra Kuniyal; Srimata Pal; Dharam Pal Singh; Sudhir Kumar Sharma; et al. (Environmental Science and Pollution Research, 2018)

Solar‐induced chlorophyll fluorescence is strongly correlated with terrestrial photosynthesis for a wide variety of biomes: First global analysis based on OCO‐2 and flux tower observations - Xing Li; Jingfeng Xiao; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2018)
Solar‐induced chlorophyll fluorescence (SIF) has been increasingly used as a proxy for terrestrial gross primary productivity (GPP). Previous work mainly evaluated the relationship between satellite‐observed SIF and gridded GPP products both based on coarse spatial resolutions. Finer resolution SIF (1.3 km × 2.25 km) measured from the Orbiting Carbon Observatory‐2 (OCO‐2) provides the first opportunity to examine the SIF–GPP relationship at the ecosystem scale using flux tower GPP data. However, it remains unclear how strong the relationship is for each biome and whether a robust, universal relationship exists across a variety of biomes. Here we conducted the first global analysis of the relationship between OCO‐2 SIF and tower GPP for a total of 64 flux sites across the globe encompassing eight major biomes. OCO‐2 SIF showed strong correlations with tower GPP at both midday and daily timescales, with the strongest relationship observed for daily SIF at the 757 nm ( R 2 = 0.72, p R 2 = 0.57–0.79, p R 2 = 0.16, p 4 grasslands and croplands than for C 3 ecosystems. The generally consistent slope of the relationship among biomes suggests a nearly universal rather than biome‐specific SIF–GPP relationship, and this finding is an important distinction and simplification compared to previous results. SIF was mainly driven by absorbed photosynthetically active radiation and was also influenced by environmental stresses (temperature and water stresses) that determine photosynthetic light use efficiency. OCO‐2 SIF generally had a better performance for predicting GPP than satellite‐derived vegetation indices and a light use efficiency model. The universal SIF–GPP relationship can potentially lead to more accurate GPP estimates regionally or globally. Our findings revealed the remarkable ability of finer resolution SIF observations from OCO‐2 and other new or future missions (e.g., TROPOMI, FLEX) for estimating terrestrial photosynthesis across a wide variety of biomes and identified their potential and limitations for ecosystem functioning and carbon cycle studies.

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

Downscaling the 2D Bénard convection equations using continuous data assimilation - M. U. Altaf; E. S. Titi; T. Gebrael; O. M. Knio; L. Zhao; M. F. McCabe; I. Hoteit (Computational Geosciences, 2017)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Trace Element Alterations in the Hair of Diabetic and Obese Women - Sameer H. Fatani; Saleh A. K. Saleh; Heba M. Adly; Altaf A. Abdulkhaliq (Biological Trace Element Research, 2016)

Visualizing uncertainties in a storm surge ensemble data assimilation and forecasting system - Thomas Höllt; M. Umer Altaf; Kyle T. Mandli; Markus Hadwiger; Clint N. Dawson; Ibrahim Hoteit (Natural Hazards, 2015)

Synthesis, spectroscopic characterization, electrochemical behavior and computational analysis of mixed diamine ligand gold(III) complexes: antiproliferative and in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; M. Monim-ul-Mehboob; Muhammad Altaf; Abdulaziz A. Al-Saadi; Mohammed I. M. Wazeer; Saleh Altuwaijri; Anvarhusein A. Isab (BioMetals, 2014)

Exploring development strategies of agricultural systems of Hill Tracts of Chittagong in Bangladesh - B. K. Bala; S. Majumder; S. M. Altaf Hossain; M. A. Haque; M. A. Hossain (Environment, Development and Sustainability, 2013)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Pituitary Adenylate Cyclase-Activating Polypeptide Prevents Cisplatin-Induced Renal Failure - Min Li; Saravanan Balamuthusamy; Altaf M. Khan; Jerome L. Maderdrut; Eric E. Simon; Vecihi Batuman (Journal of Molecular Neuroscience, 2011)

Influence of micronutrients on yeast growth and β-d-fructofuranosidase production - M. Venkateshwar; K. Chaitanya; Md. Altaf; E. J. Mahammad; Hameeda Bee; Gopal Reddy (Indian Journal of Microbiology, 2010)

Carbon dioxide, methane, and nitrous oxide exchanges in an age‐sequence of temperate pine forests - MATTHIAS PEICHL; M. ALTAF ARAIN; SAMI ULLAH; TIM R. MOORE (Global Change Biology, 2010)
We investigated soil carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) exchanges in an age‐sequence (4, 17, 32, 67 years old) of eastern white pine ( Pinus strobus L.) forests in southern Ontario, Canada, for the period of mid‐April to mid‐December in 2006 and 2007. For both CH 4 and N 2 O, we observed uptake and emission ranging from −160 to 245 μg CH 4 m −2 h −1 and −52 to 21 μg N 2 O m −2 h −1 , respectively (negative values indicate uptake). Mean fluxes from mid‐April to mid‐December across the 4, 17, 32, 67 years old stands were similar for CO 2 fluxes (259, 246, 220, and 250 mg CO 2 m −2 h −1 , respectively), without pattern for N 2 O fluxes (−3.7, 1.5, −2.2, and −7.6 μg N 2 O m −2 h −1 , respectively), whereas the uptake rates of CH 4 increased with stand age (6.4, −7.9, −10.8, and −23.3 μg CH 4 m −2 h −1 , respectively). For the same period, the combined contribution of CH 4 and N 2 O exchanges to the global warming potential (GWP) calculated from net ecosystem exchange of CO 2 and aggregated soil exchanges of CH 4 and N 2 O was on average 4%, 2 fluxes correlated positively with soil temperature but had no relationship with soil moisture. We found no control of soil temperature or soil moisture on CH 4 and N 2 O fluxes, but CH 4 emission was observed following summer rainfall events. LFH layer removal reduced CO 2 emissions by 43%, increased CH 4 uptake during dry and warm soil conditions by more than twofold, but did not affect N 2 O flux. We suggest that significant alternating sink and source potentials for both CH 4 and N 2 O may occur in N‐ and soil water‐limited forest ecosystems, which constitute a large portion of forest cover in temperate areas.

Modeling analysis of primary controls on net ecosystem productivity of seven boreal and temperate coniferous forests across a continental transect - FENGMING YUAN; M. ALTAF ARAIN; ALAN G. BARR; T. ANDREW BLACK; CHARLES P.‐A. BOURQUE; CAROLE COURSOLLE; HANK A. MARGOLIS; J. HARRY McCAUGHEY; STEVEN C. WOFSY (Global Change Biology, 2008)
Process‐based models are effective tools to synthesize and/or extrapolate measured carbon (C) exchanges from individual sites to large scales. In this study, we used a C‐ and nitrogen (N)‐cycle coupled ecosystem model named CN‐CLASS (Carbon Nitrogen‐Canadian Land Surface Scheme) to study the role of primary climatic controls and site‐specific C stocks on the net ecosystem productivity (NEP) of seven intermediate‐aged to mature coniferous forest sites across an east–west continental transect in Canada. The model was parameterized using a common set of parameters, except for two used in empirical canopy conductance–assimilation, and leaf area–sapwood relationships, and then validated using observed eddy covariance flux data. Leaf Rubisco‐N dynamics that are associated with soil–plant N cycling, and depend on canopy temperature, enabled the model to simulate site‐specific gross ecosystem productivity (GEP) reasonably well for all seven sites. Overall GEP simulations had relatively smaller differences compared with observations vs. ecosystem respiration (RE), which was the sum of many plant and soil components with larger variability and/or uncertainty associated with them. Both observed and simulated data showed that, on an annual basis, boreal forest sites were either carbon‐neutral or a weak C sink, ranging from 30 to 180 g C m −2 yr −1 ; while temperate forests were either a medium or strong C sink, ranging from 150 to 500 g C m −2 yr −1 , depending on forest age and climatic regime. Model sensitivity tests illustrated that air temperature, among climate variables, and aboveground biomass, among major C stocks, were dominant factors impacting annual NEP. Vegetation biomass effects on annual GEP, RE and NEP showed similar patterns of variability at four boreal and three temperate forests. Air temperature showed different impacts on GEP and RE, and the response varied considerably from site to site. Higher solar radiation enhanced GEP, while precipitation differences had a minor effect. Magnitude of forest litter content and soil organic matter (SOM) affected RE. SOM also affected GEP, but only at low levels of SOM, because of low N mineralization that limited soil nutrient (N) availability. The results of this study will help to evaluate the impact of future climatic changes and/or forest C stock variations on C uptake and loss in forest ecosystems growing in diverse environments.

Biodegradation of Cypermethrin by Pseudomonas in a batch activated sludge process - S. Jilani; M. Altaf Khan (International Journal of Environmental Science and Technology, 2006)

Acid Lipase of Castor Bean Lipid Bodies : Isolation and Characterisation - A. Altaf; T. V. Ankers; N. Kaderbhai; E. I. Mercer; M. A. Kaderbhai (Journal of Plant Biochemistry and Biotechnology, 1997)